PENGOMPOSAN SERABUT BUAH KELAPA SAWIT MENGGUNAKAN Aspergillus terreus SUK-1 DAN EM4 - Bakhendri Solfan; Rosmaina Rosmaina (Jurnal Agroteknologi, 2010)
Composting is a natural microbial process involving organic residues. At the end of this process, the low-value organic residues are consequently converted into higher-value products. It has become more widely accepted among those interested in organic farming, since the process is also considered as a practical alternative for use in the management of organic residues. However, the use of compost as organic fertilisers is invariably associated with the constraint in their production. The Aspergillus terreus SUK-1 is known to produce large amounts of enzyme ß-glucosidase, and thus could be effective for the degradation of cellulose. EM4 is an inoculant comprising 90% of the bacteria involved in fermentation and in lactic acid production. In this study, Aspergillus terreus SUK-1 and EM4, together with chicken dung as control, were used to determine and compare their effects on the composting of oil palm fruit fibres. The experiment design was randomized completed design with three treatments, namely Control (with chicken manure), Aspergillus terreus SUK-1 and EM4. Each treatment is replicated five times. The parameter observed was temperature, pH, humidity, carbon contents, nitrogen contents and C/N ratio. the result of this study showed that EM4 is more than effective compare to another for composting of oil palm fruit fibres. The pH, carbon contents, nitrogen contents and C/N ratio values of EM4 treatment at the end of composting were 7.53, 20.54, 2.94, 7.02, respectivel and EM4 give ideal temprature for compos process campare to Aspergillus terreus and control. Based on analyses of variance, EM4 showed significant differences with Aspergillus in temperature, nitrogen and carbon contents, while control in all parameters. for commercially purpose, EM4 is more recommended to use in composting of oil palm fruit fibres because of it is cheaper, easy to obtain in the market and high quality of composting.